2010
DOI: 10.1111/j.1556-4029.2009.01237.x
|View full text |Cite
|
Sign up to set email alerts
|

Palatine Sutures as Age Indicator: A Controlled Study in the Elderly

Abstract: Vault sutures have proven their low reliability for estimating age at death in individual forensic science cases. We broke down the palatine sutures of 134 skulls (with known sex and age at time of death) into 15 subparts and 5 stages of fusion to obtain a mean coefficient of obliteration (Cp) which was then linked to five age classes. We completed this study with multiple regression equations of total palatine suture scores. We compared our results with those obtained using the Mann method on the one hand and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 37 publications
5
17
0
2
Order By: Relevance
“…If we consider one standard deviation (1SD) in only 19.8% of the sample, it was provided a correct estimation, while considering 2SD, the success rate increases to 68.6%. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) 0.000 0.000 0.000 0.000 0.000 0.000 0.000 2 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) 0.000 1.000 0.000 0.000 0.000 0.000 0.000 3 (35)(36)(37)(38)(39)(40)(41)(42)(43)(44) 0.000 0.000 0.000 0.428 0.000 0.000 0.000 4 (45)(46)(47)(48)(49)(50)(51)(52)(53)(54) 0.000 0.000 0.000 0.428 0.045 0.000 0.000 5 (55)(56)(57)(58)(59)(60)(61)(62)(63)(64) 0.000 0.000 0.000 0.143 0.348 0.000 ...…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If we consider one standard deviation (1SD) in only 19.8% of the sample, it was provided a correct estimation, while considering 2SD, the success rate increases to 68.6%. (15)(16)(17)(18)(19)(20)(21)(22)(23)(24) 0.000 0.000 0.000 0.000 0.000 0.000 0.000 2 (25)(26)(27)(28)(29)(30)(31)(32)(33)(34) 0.000 1.000 0.000 0.000 0.000 0.000 0.000 3 (35)(36)(37)(38)(39)(40)(41)(42)(43)(44) 0.000 0.000 0.000 0.428 0.000 0.000 0.000 4 (45)(46)(47)(48)(49)(50)(51)(52)(53)(54) 0.000 0.000 0.000 0.428 0.045 0.000 0.000 5 (55)(56)(57)(58)(59)(60)(61)(62)(63)(64) 0.000 0.000 0.000 0.143 0.348 0.000 ...…”
Section: Discussionmentioning
confidence: 99%
“…The following methods were applied to each skeleton (depending on the availability of their relative skeletal traits) by one single experienced observer: the Suchey–Brooks (SB) method for the pubic symphysis (PS) , the Lovejoy method for the auricular surface (AS) of the ilium , the Işcan (IC) method for the fourth rib , the Rougé‐Maillart method for the acetabulum combined with the auricular surface (A+AS) , and the Beauthier method for the obliteration of palatine sutures . The choice of which methods to use in this study fell on those considered most common by the literature and also suggested by some guidelines according to Cunha et al , such as PS, AS, and SB.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the adult population age ranged from young to old adults according to the availability of the sample once they have been selected by sex. Sex and age were determined according to standard anthropological methods (Beauthier et al, ; Brooks & Suchey, ; Buikstra & Ubelaker, ; İşcan, Loth, & Wright, ; Rougé‐Maillart et al, ) applied to the entire skeleton.…”
Section: Methodsmentioning
confidence: 99%
“…The hard palate is very often well preserved in human remains and its sutures are a well-known feature allowing to estimate an individual's age [1,23]. Taking into account that the latter is the most difficult part of the forensic examination, the hard palate might also be suitable for gender determination, as it has a number of characteristic anatomical points which allow conducting easy and repeatable measurements.…”
Section: Introductionmentioning
confidence: 99%